Color Stability of Glass Ionomer Cement after Reinforced with Two Different Nanoparticles - Sharat Chandra Pani; Moath Tofik Aljammaz; Abdullah Mohammed Alrugi; Abdulaziz Mohammed Aljumaah; Yazeed Minahi Alkahtani; Abdulaziz AlKhuraif (International Journal of Dentistry)
Aim. This study aimed to compare the staining characteristics of a commercially available restorative glass ionomer cement to a formulation reinforced by the addition of carbon nanotubes and another formulation reinforced by the addition of silver nanoparticles to the powder of the same cement. Methodology. Twenty samples each of a control glass ionomer cement (PULPDENT® Glass Fill®, Pulpdent Corp. Watertown, MA, USA), control cement reinforced with 0.0006 gm (0.03% by weight) of carbon nanotubes (Sigma Aldrich, St Louis MO, USA), and control cement reinforced with 0.2 gm (10% by weight) of silver nanoparticles (Nanocyl™, Nanocyl SA, Sambreville, Belgium) were immersed in a staining solution. Color evaluations were carried out after 1 h, 24 h, and 1 week. Color change values were calculated. Results. The results indicated that carbon nanotube reinforced specimens exhibited less color stability when compared to controlled glass ionomer cement specimens; however, both samples had significantly greater color stability than silver nanoparticle reinforced glass ionomer samples. Conclusion. It can be concluded within the limitations of this study that carbon nanotube reinforced glass ionomer cements have better color stability than silver nanoparticle reinforced glass ionomer cements.